Estimation of the costs attributable to vitamin K antagonist treatment in patients with non-valvular atrial fibrillation from a French societal perspective. Issue 1 (1st January 2019) - Levy, Pierre; Smadja, David; Dorey, Julie; Toumi, Mondher; Meinecke, Anna-Katharina; Bowrin, Kevin; Briere, Jean-Baptiste
ABSTRACT: Background : Little is known about the costs associated with vitamin K antagonist (VKA) treatment in patients with non-valvular atrial fibrillation (NVAF) in France. Objectives : To evaluate monthly per-patient costs attributable to VKA treatment in NVAF patients from a French societal perspective. Study design : Retrospective data were obtained from 7 international normalised ratio (INR) monitoring centres in France. Patients older than 18 years of age with NVAF treated with VKA were recruited. Additional patient-level data assessing resource use corresponding with VKA treatment were collected via self-completed questionnaires. Unit costs applicable to 2015 were multiplied by resource use and summed to generate VKA treatment costs. Results : 363 patients were included; 53% were men. The majority of patients received fluindione (72%). The number of INR tests per patient per month was 1.69 (95% CI, 1.59–1.80). The monthly patient cost was €39.72 (€36.23–43.21) from the French societal perspective. Direct medical costs comprised 76% of overall costs, with drug costs representing 7.4% (€2.4); direct non-medical and indirect costs comprised 10% and 14% respectively. Conclusions : Costs associated with VKA treatment in NVAF cannot be estimated only with drug costs. When direct and indirect attributable costs associated with VKA treatment are considered, the VKA treatment costs are more substantial.